China’s Monetary Challenges Past Experiences and Future Prospects - Burdekin, Richard C. K (Cambridge University Press, 2013)
Work on this book was funded by a 2005–2006 Scholar Grant from the Chiang Ching-kuo Foundation, and I am immeasurably grateful for this support. Some of the initial research was conducted while I was a Visiting Senior Fellow at Hawaii’s East-West Center, which provided a very hospitable and helpful environment for my work. My home institution, Claremont McKenna College, also helped with support for databases and other research needs.